Enhancing Farmers’ Knowledge and Sustainable Agriculture through Coconut Husk Utilization in Kalikur Village - Butarbutar, Pesalmen; Pratama, Agief Julio; Nurulhaq, M. Iqbal; Budiarto, Tri; Situmeang, Widya Hasian; Dewi, Ratih Kemala; Mumpuni, Restu Puji; Wiraguna, Edi (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This program aimed to enhance farmers' knowledge of coconut husk waste management by transforming it into cocopeat, an eco-friendly planting medium. The initiative sought to promote sustainable agriculture and provide economic benefits for the community. Method: A participatory approach was used, involving community engagement through observation, socialization, training, and hands-on practice. The process included theoretical discussions, practical demonstrations, and knowledge assessments through pre- and post-tests. Practical Applications: Farmers learned to convert coconut husks into cocopeat using simple tools. The training increased awareness of waste management and provided an alternative planting medium with high water retention and nutrient content, benefiting agricultural productivity. Conclusion: The program successfully increased participants’ knowledge by 57%, demonstrating the effectiveness of agricultural extension in improving local resource utilization. Future efforts should focus on continued training and mentorship to ensure sustainable implementation and long-term benefits.